Dielectric Elastomer Based "Grippers" for Soft Robotics. (29th September 2015) - Shian, Samuel; Bertoldi, Katia; Clarke, David R.
Abstract : The use of few stiff fibers to control the deformation of dielectric elastomer actuators, in particular to break the symmetry of equi‐biaxial lateral strain in the absence of prestretch, is demonstrated. Actuators with patterned fibers are shown to evolve into unique shapes upon electrical actuation, enabling novel designs of gripping actuators for soft robotics.